Annotated checklist of Bryobionta of the LivoberezhnePolissja (Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
The list of bryophyta species of LivoberezhnePolissja ( within the limits of Kiev, Chernigov and Sumy regions of Ukraine) is given. For each species the place and time of collection and short characteristics of habitats, collectors are pointed out. Besides the author's materials, herbarium data (KW, KHER) are presented, which were looked through by the author of the article as well as literature data. The species are ranged according to the system, adopted in the Checklist of Bryophyta of Ukraine (2008).
Keywords: Bryobionta, LivoberezhnePolissja, Ukraine.